RECEPTION OF ÉMILE DURKHEIM’S IDEA OF EDUCATION AS SOCIAL INSTITUTE - Tatiana I. Barsukova (Вестник Северо-Кавказского федерального университета)
The article provides a scientific proof to the possibility of employing institutional approach when dealing with education. The theoretical-methodological basis for the analysis lies in the postulates and methodology used in relation to this phenomenon in the works by Émile Durkheim.